2011
DOI: 10.1002/ajmg.a.33875
|View full text |Cite
|
Sign up to set email alerts
|

Deletion 2p15–16.1 syndrome: Case report and review

Abstract: We report on a 9-year-old female patient with facial anomalies and developmental delay, heterozygous for three de novo rearrangements: a paracentric inversion of chromosome 7, an apparently balanced translocation between chromosome 1 and 7, involving the same inverted chromosome 7, detected by standard cytogenetic analysis [46,XX, der(7) inv(7)(q21.1q32.1)t(1;7)(q23q32.1)]; and a 2p16.1 deletion, spanning about 3.5 Mb of genomic DNA, shown by SNP-array analysis [arr 2p16.1 (56,706,666-60,234,485)x1 dn]. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
0
29
1
Order By: Relevance
“…Conversely, three patients with deletions in the same region of 2p15-16.1, but not involving BCL11A, did not reveal abnormalities on their imaging studies (Fig. 2) [Chabchoub et al, 2008;Fannemel and Barøy, 2014;Prontera et al, 2011]. The only other described patient in the literature with a microdeletion similar to this case, i.e.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Conversely, three patients with deletions in the same region of 2p15-16.1, but not involving BCL11A, did not reveal abnormalities on their imaging studies (Fig. 2) [Chabchoub et al, 2008;Fannemel and Barøy, 2014;Prontera et al, 2011]. The only other described patient in the literature with a microdeletion similar to this case, i.e.…”
Section: Discussioncontrasting
confidence: 51%
“…Following the initial report in 2007 by Rajcan-Separovic et al [Rajcan-Separovic et al, 2007], there have been 15 patients reported in the literature with overlapping deletions in this region [Chabchoub et al, 2008;Fannemel and Barøy, 2014;Florisson et al, 2013;Félix and Petrin, 2010;Hancarova et al, 2013;Hucthagowder et al, 2012;Liang et al, 2009;Peter et al, 2014;Piccione et al, 2012;Prontera et al, 2011;de Leeuw et al, 2008], in addition to reports from public databases such as DECIPHER and ISCA [Firth et al, 2009;Miller et al, 2010] and other large studies assessing developmental delay and copy number variants [Cooper et al, 2011;Kaminsky et al, 2011]. All of the reported patients had varying degrees of developmental delay, along with shared dysmorphic features and microcephaly, making this a recognizable microdeletion syndrome.…”
Section: Introductionmentioning
confidence: 97%
“…1. It is of interest to note that even without an obvious deletion of BCL11A, fetal hemoglobin expression was increased in a patient with isolated FANCL and VRK2 deletions (11,35), possibly suggesting an effect of the distant deletion on the function of BCL11A. Regulatory SNPs were previously reported in the enhancer sequence that lies in the second intron of BCL11A and were associated with increased expression of fetal hemoglobin as well as with schizophrenia and attention deficit hyperactivity disorder (ADHD) (4).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The first is a 15-year-old female with a 3.5-Mb deletion downstream of BCL11A ( Figure 1A). 13 The second and third are an 8-year-old female and 7-year-old male with 642-kb and 2.5-Mb deletions, respectively, covering the entire BCL11A gene ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…12,13 The first is a 15-year-old female with a 3.5-Mb deletion downstream of BCL11A ( Figure 1A). 13 The second and third are an 8-year-old female and 7-year-old male with 642-kb and 2.5-Mb deletions, respectively, covering the entire BCL11A gene ( Figure 1A). 12 Although their neurological and physical traits have been extensively characterized, their hematopoietic profiles have not been previously assessed.…”
Section: Resultsmentioning
confidence: 99%